Effect of Platelet-activating Factor on in vitro and in vivo Interleukin-6 Production - B. Pignol; T. Maisonnet; P. Guinot; J. M. Mencia-Huertac; P. Braquet (Mediators of Inflammation)
The aim of the present study was to investigate the possible effect of platelet-activating factor (PAF), by comparison with interleukin-1β and polyriboinositic/polyribocytidylic (poly I–C) acid, on IL-6 production by L 929 mouse fibroblasts. At concentrations above 1 μM PAF, the production of IL-6 by mouse fibroblasts was enhanced in a dose dependent fashion. At 5 μM PAF, the peak increase (60.1 ± 19.4 U/ml) was similar to that induced by 50 μg/ml poly I–C (60.0 ± 35.0 U/ml) and higher than the one evoked by 100 U/ml IL-1β (3.8 ± 1.8 U/ml). The increase of 11-6 activity induced by 5 μM PAF was maximal after a 22 h incubation period with L 929 cells. Lyso-PAF (5 μM) also increased IL-6 activity from fibroblasts to a similar extent compared with 5 μM PAF. In addition, the IL-6 activity induced by 5 μM PAF was still observed when the specific PAF antagonist, BN 52021 (10 μM), was added to the incubation medium of L 929 cells. The result suggests that the production of IL-6 by L 929 cells evoked by PAF in vitro is not receptor mediated. The in vivo effect of PAF on IL-6 production was also investigated in the rat. Two hours after intravenous injection of PAF (2 to 4 μg/kg), a dramatic increase of IL-6 activity in rat serum was observed, this effect being dose dependent. The increase of IL-6 induced by 3 μg/kg PAF was not observed when the animals were treated with the PAF antagonist, BN 52021 (1 to 60 mg/kg0. These results demonstrate that PAF modulates IL-6 production and that the in vivo effect is receptor mediated.